Gambling harms, stigmatisation and discrimination: A qualitative naturalistic forum analysis. - Katy Penfold; Laura Louise Nicklin; Darren Chadwick; Joanne Lloyd (PLoS ONE)
People who experience gambling harms commonly experience stigmatisation, which is detrimental to psychological wellbeing, and a significant barrier to help-seeking. While there have been efforts to challenge stigmatisation, there is little empirical evidence available to inform such initiatives. To address this gap in knowledge, we conducted a thematic analysis of naturalistic data in the form of posts made on online support forums by people with experience of gambling-related harm, in order to understand how they are stigmatised, and to identify barriers to help-seeking. Five main themes were identified: (a) beliefs about the nature and origin of gambling addiction, which related to participants' beliefs about causes of gambling harm and cognitions about the nature of addiction; (b) self-stigma, which encompassed the frequent and substantial incidences of self-stigma; (c) anticipated stigma, which described the stigma and discrimination people expected to face because of their gambling harm; (d) stigmatising other people who experience gambling harm, which describes the ways in which some people who experienced gambling harms stigmatised other people who experienced gambling harms; and (e) experienced stigma and discrimination, which encompassed the experienced stigmatisation people encountered. Experiences discussed/described within the forums were developed into a timeline of gambling harms which was cyclical in nature and involved six stages: onset, concealment of problems, crisis point, disclosure of problems, recurrence of harms (sometimes termed 'relapse') and recovery. The study highlights the impact of societal stigma on individuals' self-perception and interactions, particularly emphasising the challenges experienced during relapse periods, which heighten stigma and distress. The study also identifies potential avenues for stigma reduction, including targeted campaigns addressing societal, anticipated, and self-stigma.